FACTORS AFFECTING ENF BASED TIME-OF-RECORDING ESTIMATION FOR VIDEO - Vatansever, Saffet; Dirik, Ahmet Emir; Memon, Nasir (Ieee, 2019)
ENF (Electric Network Frequency) oscillates around a nominal value (50/60 Hz) due to imbalance between consumed and generated power. The intensity of a light source powered by mains electricity varies depending on the ENF fluctuations. These fluctuations can be extracted from videos recorded in the presence of mains-powered source illumination. This work investigates how the quality of the ENF signal estimated from video is affected by different light source illumination, compression ratios, and by social media encoding. Also explored is the effect of the length of the ENF ground-truth database on time of recording detection and verification.
44th IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) -- MAY 12-17, 2019 -- Brighton, ENGLAND
Keywords: ENF; electric network frequency; video forensics; time-of-recording